Managing the evolution of cooperation - Julian Dormann; Thomas Ehrmann (Max Planck Institute of Economics, 2008)
Management scholars have long stressed the importance of evolutionary processses for inter-firm cooperation but have mostly missed the promising opportunity to incorporate ideas from evolutionary theories into the analysis of collaborative arrangements. In this paper, we first present three rules for the evolution of cooperation - kinship selection, direct reciprocity, and indirect reciprocity. Second, we apply our theoretical considerations, enriched with ideas from cultural anthropology, to the context of a specific and particularly attractive type of cooperative arrangement, the franchise form of organization. Third, we provide a preliminary empirical test with regards to conditions under which evolutionary modes can secure cooperative behavior. We conclude by summarizing our results and deriving fertile areas for further research.
Keywords: 330; Unternehmenskooperation; Evolutionsökonomik; Ethnologie; Franchising; Theorie; Deutschland